Characterization of smallest active monomeric penicillin V acylase from new source: a yeast, rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Prabhune, Asmita; Suresh, C. G.; Pundle, Archana (Process Biochemistry, 2008)
An intracellular monomeric penicillin V acylase (PVA) of 36,000 Da exhibiting pI of 4.19, purified from newly identified yeast source, Rhodotorula aurantiaca (NCIM 3425). The enzyme was purified by hydrophobic interaction chromatography. The enzyme showed optimal activity at 45 degrees C and retained 80% activity after incubation at 45 degrees C and pH 5.5 for I h. The enzyme showed maximum activity at pH 5.5 and was very stable between pH 5.5-6.5 with optimum stability at pH 6.0. It exhibited 50% of its original activity after 30 min incubation at 60 degrees C. Enzyme hydrolyzed substrates with benzyl side chain but preferred penicillin V as primary substrate. N-terminally located serine supports the fact that it belongs to Ntn (N-terminal nucleophile)-hydrolase superfamily. The initial ten amino acid residues of R. aurantiaca PVA were identical to the initial sequence of NADH dehydrogenase (EC 1.6.99.3): however the enzyme lacks dehydrogenase activity. EGTA, EDTA, hexane and ethyl acetate stabilized the activity where as small chain alcohols inhibited it. 1,4-Dioxane, THF (tetrahydrofurane), phenol and benzyl alcohol severely inhibited enzyme activity while BME and DTT increased it. Tween 80 and Tween 20 highly enhanced the activity where as SIDS and Triton X-100 inhibited it. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Intracellular enzyme; N-terminal sequencing; Penicillin V acylase; Purification; Rhodotorula aurantiaca; Substrate specificity

Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Permeabilization effect of organic solvents on cell bound penicillin v acylase activity of Erwinia aroideae (DSMZ 30186) - Kumar, Atul; Pundle, Archana (Journal of Biotechnology, 2008)

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Effect of organic solvents on cell-bound penicillin V acylase activity of erwinia aroideae (DSMZ 30186): a permeabilization effect - Kumar, Atul; Pundle, Archana (Journal of Molecular Catalysis B-Enzymatic, 2009)
Erwinia aroideae (DSMZ 30186) is a potential microbial culture to produce intracellular penicillin V acylase (PVA). The whole cell PVA activity was improved by permeabilization with various organic solvents. The cell-bound PVA activity showed an eightfold increase upon treatment with chloroform (5 mu L/mg(dry) (biomass)) for 10 min and diethyl ether (10 mu L/mg(dry) (biomass)) for 45 min. Hexane, toluene, ethyl acetate and dichloromethane enhanced the enzyme activity up to two-, six-, four- and two-fold, respectively; whereas, PVA activity declined drastically on permeabilization with acetone, pyridine and alcohols. The physicochemical properties of the organic solvents used for permeabilization were correlated with the change in activity. It was found that solvents with high hydrophobicity (log P > 0.68) and lower dielectric constant (< 9) were relatively effective in increasing PVA activity. These results allow systematic selection of suitable solvent for best performance. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Erwinia aroideae; Hydrophobicity; Organic solvents; Penicillin V acylase; Permeabilization

Rhodotorula aurantiaca penicillin V acylase: active site characterization and fluorometric studies - Kumar, Atul; Gowda, Nagaraj M.; Gaikwad, Sushama M.; Pundle, Archana (Journal of Photochemistry and Photobiology B-Biology, 2009)
Penicillin V acylase (PVA), a member of newly evolved Ntn-hydrolase superfamily, is a pharmaceutically important enzyme to produce 6-aminopenicillanic acid. Active site characterization of recently purified monomeric PVA from Rhodotorula aurantiaca (Ra-PVA), the yeast source, showed the involvement of serine and tryptophan in the enzyme activity. Modification of the protein with serine and tryptophan specific reagents such as PMSF and NBS showed partial loss of PVA activity and substrate protection. Ra-PVA was found to be a multi-tryptophan protein exhibiting one tryptophan, in native and, four in its denatured condition. Various solute quenchers and substrate were used to probe the microenvironment of the putative reactive tryptophan through fluorescence quenching. The results obtained indicate that the tryptophan residues of Ra-PVA were largely buried in hydrophobic core of the protein matrix. Quenching of the fluorescence by acrylamide was collisional. Acrylamide was the most effective quencher amongst all the used quenchers, which quenched 71.6% of the total intrinsic fluorescence of the protein, at a very less final concentration of 0.1 M. Surface tryptophan residues were found to have predominantly more electropositively charged amino acids around them, however differentially accessible for ionic quenchers. Denaturation led to shift lambda(max) from 336, in native state, to 357 nm and more exposed to the solvent, consequently increase in fluorescence quenching with all quenchers. This is an attempt towards the conformational studies of Ra-PVA. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: active site residues; Fluorometric studies; Penicillin V acylase; Rhodotorula aurantiaca

Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Penicillin V acylase from pectobacterium atrosepticum exhibits high specific activity and unique kinetics - Avinash, Vellore Sunder; Ramasamy, Sureshkumar; Suresh, C. G.; Pundle, Archana (International Journal of Biological Macromolecules, 2015)
Penicillin V acylases (PVAs, E.C.3.5.11) belong to the Ntn hydrolase super family of enzymes that catalyze the deacylation of the side chain from phenoxymethyl penicillin (penicillin V). Penicillin acylases find use in the pharmaceutical industry for the production of semi-synthetic antibiotics. PVAs employ the N-terminal cysteine residue as catalytic nucleophile and are structurally and evolutionarily related to bile salt hydrolases (BSHs). Here, we report the cloning and characterization of a PVA enzyme from the Gram-negative plant pathogen, Pectobacterium atrosepticum (PaPVA). The enzyme was cloned and expressed in Escherichia coli attaining a very high yield (250 mg/l) and a comparatively high specific activity (430 IU/mg). The enzyme showed marginally better pH and thermo-stability over PVAs characterized from Gram-positive bacteria. The enzyme also showed enhanced activity in presence of organic solvents and detergents. The enzyme kinetics turned out to be significantly different from that of previously reported PVAs, displaying positive cooperativity and substrate inhibition. The presence of bile salts had a modulating effect on PaPVA activity. Sequence analysis and characterization reveal the distinctive nature of these enzymes and underscore the need to study PVAs from Gram-negative bacteria. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cooperative; Enzyme kinetics; Gram-negative; Penicillin V acylase; Substrate inhibition

Structural analysis of a penicillin V acylase from pectobacterium atrosepticum confirms the importance of two Trp residues for activity and specificity - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Chand, Deepak; Pundle, Archana; Suresh, Cheravakattu Gopalan; Ramasamy, Sureshkumar (Journal of Structural Biology, 2016)
Penicillin V acylases (PVA) catalyze the deacylation of the beta-lactam antibiotic phenoxymethylpenicillin (Pen V). They are members of the Ntn hydrolase family and possess an N-terminal cysteine as the main catalytic nucleophile residue. They form the evolutionarily related cholylglycine hydrolase (CGH) group which includes bile salt hydrolases (BSH) responsible for bile deconjugation. Even though a few PVA and BSH structures have been reported, no structure of a functional PVA from Gram-negative bacteria is available. Here, we report the crystal structure of a highly active PVA from Gram-negative Pectobacterium atrosepticum (PaPVA) at 2.5 angstrom resolution. Structural comparison with PVAs from Gram-positive bacteria revealed that PaPVA had a distinctive tetrameric structure and active site organization. In addition, mutagenesis of key active site residues and biochemical characterization of the resultant variants elucidated the role of these residues in substrate binding and catalysis. The importance of residue Trp23 and Trp87 side chains in binding and correct positioning of Pen V by PVAs was confirmed using mutagenesis and substrate docking with a 15 ns molecular dynamics simulation. These results establish the unique nature of Gram-negative CGHs and necessitate further research about their substrate spectrum. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Aromatic stacking; Cholylglycine hydrolase; molecular dynamics; Mutagenesis; Oligomeric interactions

Biotransformation of penicillin V to 6-aminopenicillanic acid using immobilized whole cells of E. coli expressing a highly active penicillin V acylase - Avinash, Vellore Sunder; Chauhan, Palna Dinesh; Gaikwad, Shraddha; Pundle, Archana (Preparative Biochemistry & Biotechnology, 2017)
The production of 6-aminopenicillanic acid (6-APA) is a key step in the manufacture of semisynthetic antibiotics in the pharmaceutical industry. The penicillin G acylase from Escherichia coli has long been utilized for this purpose. However, the use of penicillin V acylases (PVA) presents some advantages including better stability and higher conversion rates. The industrial application of PVAs has so far been limited due to the nonavailability of suitable bacterial strains and cost issues. In this study, whole-cell immobilization of a recombinant PVA enzyme from Pectobacterium atrosepticum expressed in E. coli was performed. Membrane permeabilization with detergent was used to enhance the cell-bound PVA activity, and the cells were encapsulated in calcium alginate beads and cross-linked with glutaraldehyde. Optimization of parameters for the biotransformation by immobilized cells showed that full conversion of pen V to 6-APA could be achieved within 1 hr at pH 5.0 and 35 degrees C, till 4% (w/v) concentration of the substrate. The beads could be stored for 28 days at 4 degrees C with minimal loss in activity and were reusable up to 10 cycles with 1-hr hardening in CaCl2 between each cycle. The high enzyme productivity of the PVA enzyme system makes a promising case for its application for 6-APA production in the industry.

Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa - Sunder, Avinash Vellore; Utari, Putri Dwi; Ramasamy, Sureshkumar; van Merkerk, Ronald; Quax, Wim; Pundle, Archana (Applied Microbiology and Biotechnology, 2017)
Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the natural physiology of their native microbes is not clearly understood. This report details the characterization of AHL degradation activity by homotetrameric PVAs from two gram-negative plant pathogenic bacteria, Pectobacterium atrosepticum (PaPVA) and Agrobacterium tumefaciens (AtPVA). Both the PVAs exhibited substrate specificity for degrading long-chain AHLs. Exogenous addition of these enzymes into Pseudomonas aeruginosa greatly diminished the production of elastase and pyocyanin and biofilm formation and increased the survival rate in an insect model of acute infection. Subtle structural differences in the PVA active site that regulate specificity for acyl chain length have been characterized, which could reflect the evolution of AHL-degrading acylases in relation to the environment of the bacteria that produce them and also provide strategies for enzyme engineering. The potential for using these enzymes as therapeutic agents in clinical applications and a few ideas about their possible significance in microbial physiology have also been discussed.
Keywords: N-acylhomoserine lactone acylase; Ntn hydrolase; pathogenesis; Penicillin Vacylase; Quorum quenching

Process development for 6-aminopenicillanic acid production using lentikats-encapsulated escherichia coli cells expressing penicillin V acylase - Sawant, Amol M.; Sunder, Avinash Vellore; Vamkudoth, Koteswara Rao; Ramasamy, Sureshkumar; Pundle, Archana (ACS Omega, 2020)
Penicillin V acylase (PVA, EC 3.5.1.11) hydrolyzes the side chain of phenoxymethylpenicillin (Pen V) and finds application in the manufacture of the pharmaceutical intermediate 6-aminopenicillanic acid (6-APA). Here, we report the scale-up of cultivation of Escherichia coli whole cells expressing a highly active PVA from Pectobacterium atrosepticum and their encapsulation in polyvinyl alcohol-poly(ethylene glycol) Lentikats hydrogels. A biocatalytic process for the hydrolysis of 2% (w/v) Pen V was set up in a 2 L reactor using the Lentikats-immobilized whole cells, with a customized setup to enable continuous downstream processing of the reaction products. The biocatalytic reaction afforded complete conversion of Pen V for 10 reaction cycles, with an overall 90% conversion up to 50 cycles. The bioprocess was further scaled up to the pilot-scale at 10 L, enabling complete conversion of Pen V to 6-APA for 10 cycles. The 6-APA and phenoxy acetic acid products were recovered from downstream processing with isolated yields of 85-90 and 87-92%, respectively. Immobilization in Lentikats beads improved the stability of the whole cells on storage, maintaining 90-100% activity and similar conversion efficiency after 3 months at 4 degrees C. The robust PVA biocatalyst can be employed in a continuous process to provide a sustainable route for bulk 6-APA production from Pen V.